Circulating B Cells With Memory and Antibody-Secreting Phenotypes Are Detectable in Pediatric Kidney Transplant Recipients Before the Development of Antibody-Mediated Rejection. Issue 9 (September 2019) - Fischman, Clara; Fribourg, Miguel; Fabrizio, Ginevri; Cioni, Michela; Comoli, Patrizia; Nocera, Arcangelo; Cardillo, Massimo; Cantarelli, Chiara; Gallon, Lorenzo; Petrosyan, Astgik; Da Sacco, Stefano; Perin, Laura; et al.
Abstract : Background: Development of anti–human leukocyte antigen donor-specific antibodies (DSAs) is associated with antibody-mediated rejection (AMR) and reduced allograft survival in kidney transplant recipients. Whether changes in circulating lymphocytes anticipate DSA or AMR development is unclear. Methods: We used time-of-flight mass cytometry to analyze prospectively collected peripheral blood mononuclear cells (PBMC) from pediatric kidney transplant recipients who developed DSA (DSA-positive recipients [DSA POS ], n = 10). PBMC were obtained at 2 months posttransplant, 3 months before DSA development, and at DSA detection. PBMC collected at the same time points posttransplant from recipients who did not develop DSA (DSA-negative recipients [DSA NEG ], n = 11) were used as controls. Results: DSA POS and DSA NEG recipients had similar baseline characteristics and comparable frequencies of total B and T cells. Within DSA POS recipients, there was no difference in DSA levels (mean fluorescence intensity [MFI]: 13 687 ± 4159 vs 11 375 ± 1894 in DSA POS AMR-positive recipients (AMR POS ) vs DSA POS AMR-negative recipients (AMR NEG ), respectively; P = 0.630), C1q binding (5 DSA POS AMR POS [100%] vs 4 DSA POS AMR NEG [80%]; P = 1.000), or C3d binding (3 DSA POS AMR POS [60%] vs 1 DSA POS AMR NEG [20%]; P = 0.520) between patients who developed AMR and those who did not. However, DSA POS patients who developed AMR (n = 5; 18.0 ± 3.6 mo post-DSA detection) had increased B cells with antibody-secreting (IgD − CD27 + CD38 + ; P = 0.002) and memory (IgD - CD27 + CD38 − ; P = 0.003) phenotypes compared with DSA NEG and DSA POS AMR NEG recipients at DSA detection. Conclusions: Despite the small sample size, our comprehensive phenotypic analyses show that circulating B cells with memory and antibody-secreting phenotypes are present at DSA onset, >1 year before biopsy-proven AMR in pediatric kidney transplant recipients. Abstract : Supplemental Digital Content is available in the text.